Handbook of research on deep learning innovations and trends - Hassanien, Aboul Ella 1964-; Darwish, Ashraf; Chowdhary, Chiranji Lal (IGI Global, 2019)
"This book explores the application of deep learning in various areas like computer vision, image processing, biometrics, pattern recognition and medical imaging, and other real-world applications"...
Includes bibliographical references
Keywords: Artificial intelligence -- Handbooks, manuals, etc; Machine learning -- Handbooks, manuals, etc; Neural networks (Computer science) -- Handbooks, manuals, etc; Künstliche Intelligenz; Methode; Deep Learning; Computersicherheit; Maschinelles Lernen; Anwendung